Byond BSI Customer Satisfaction Determinants: Interface Design, User Experience, and Ease of Use - Yanuar Wendy Wardana (Journal of Islamic Digital Economic and Finance, 2025)
Introduction: Data from the Financial Services Authority (OJK) shows that the number of mobile banking users in Indonesia reached 147.8 million users in 2023, increasing 23.4% from the previous year. Customer satisfaction in mobile banking applications becomes a critical factor determining the success of Islamic banking digital transformation, as 73% of customers will switch banks after poor mobile banking experiences. Objective: This research aims to analyze the influence of interface design, user experience, and ease of use on customer satisfaction of the Byond BSI mobile banking application and identify the most dominant factor in shaping user satisfaction. Method: This research uses a quantitative research method with snowball sampling technique, resulting in 100 respondents who are active customers of Bank Syariah Indonesia using Byond BSI application. Data analysis includes validity and reliability tests, classical assumption tests, and multiple linear regression analysis. Result: The findings show that interface design, user experience, and ease of use have positive and significant influences on customer satisfaction of the Byond BSI application. All three independent variables prove to be fundamental determinants in enhancing customer satisfaction and competitive advantage in Indonesia's Islamic digital banking market. Implication: This suggests that combining interface design optimization that prioritizes visual consistency and intuitive navigation, user experience development integrating functional efficiency with pleasant experiences, and ease of use enhancement through transaction process simplification serves as strategic framework for Islamic banking digitalization.